The European Union Counteraction To Israel's Settlement Policy In The Occupied Arab Territories: Myths And Realities - Krylov, A. V. (Vestnik MGIMO-Universiteta, 2014)
More than 50 years the European Union member states (the European Economic Community up to 1993) maintain a special relations with Israel particularly in the trade sphere. Only in 2014 the export of Israeli products to Europe increased by 3%, amounting in absolute terms to a third of total exports of Israel. At the same time, the position of the EU with regard to the Palestinian-Israeli conflict is clearly contrary to the real character of the mutual economic, scientific and technical cooperation. After the failure in 2001 of the Palestinian-Israeli negotiations aimed to reach a «Final-Status Agreement» in accordance with the Oslo Accords, the European Union made several attempts to limit the European market penetration of the Israeli products originating from the occupied territories (the West Bank, Gaza Strip, East Jerusalem and the Golan Heights). However, as can be seen from the contents of the article, there is no consensus between the EU member states with regard to the Israeli settlement policy. The study argues that all the decisions made so far in the European Union to limit Israeli export or reduce crediting of programs for scientific and technical cooperation used to be of declarative or vague character.